PERANCANGAN SISTEM INFORMASI PENGELOLAAN INVENTARIS BERBASIS WEBSITE PADA SMK PGRI PEKANBARU - Putri, Aulia; Rini, Faiza; Samudra, Ami Anggraini (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Efficient inventory management is a primary need in an educational environment. SMK PGRI Pekanbaru, as one of the vocational high schools in Pekanbaru City, Riau Province, still records borrowing and returning and inventory reporting conventionally. This study uses the System Development Life Cycle (SDLC) methodology with an Iterative model, which includes the stages of analysis, design, implementation, testing, and development. This system provides various functions, such as recording inventory items, borrowing, returning and borrowing history reports. Testing was carried out through alpha and beta tests, where the results of the alpha test showed that the system was running well or valid. Meanwhile, the beta test involving expert validation obtained an average score of 89.54% with a very good category, while user validation showed an average result of 95.46%, also with a very good category. Thus, it can be concluded that this asset management information system is feasible to use. The results of the study indicate that this system can improve efficiency and accuracy in inventory management, simplify the borrowing process and loan reports, and increase transparency through features that allow reports to be accessed by managers and supervisors. It is expected that this system will be an effective solution in improving inventory management at SMK PGRI Pekanbaru.